A multicountry assessment in Eurasia: Alignment of physician perspectives on palliative care integration in pediatric oncology with World Health Organization guidelines. Issue 16 (12th June 2020) - Ehrlich, Bella S.; Movsisyan, Narine; Batmunkh, Tsetsegsaikhan; Kumirova, Ella; Borisevich, Marina V.; Kirgizov, Kirill; Graetz, Dylan E.; McNeil, Michael J.; Yakimkova, Taisiya; Vinitsky, Anna; Ferrara, Gia; Li, Chen; et al.
Abstract : Background: The World Health Organization (WHO) advocates for early integration of palliative care for all children with life‐threatening illness. Provider awareness and misperceptions, however, can impede this imperative. In the Eurasian region, little is known about physician knowledge and perspectives on palliative care. Methods: The Assessing Doctors' Attitudes on Palliative Treatment survey was developed as an evidence‐based and culturally relevant assessment of physician perceptions on palliative care integration into childhood cancer care in Eurasia. Iteratively tested by American and Eurasian palliative care experts, the survey was culturally adapted, translated, and piloted in English, Russian, and Mongolian. The survey was distributed to physicians caring for children with cancer. Fifteen statements were scored in accordance with WHO guidelines to evaluate provider knowledge. The statistical analysis was complemented by a qualitative analysis of open‐ended responses. Results: This study received 424 responses from 11 countries in Eurasia. The mean alignment between provider perspectives and WHO recommendations was 70% (range, 7%‐100%). Significant independent predictors of higher alignment included country, prior palliative care education, and greater experience with patient death. Respondents primarily described palliative care as end‐of‐life care and symptom management. Two‐thirds of respondents (67%) reported not feeling confident about delivering at least 1 component of palliative care. Conclusions: This is the first study assessing physician perspectives and knowledge of palliative care in Eurasia and reveals wide variability in alignment with WHO guidelines and limited confidence in providing palliative care. Study findings will inform targeted educational interventions, which must be tailored to the local political, economic, and cultural context. Abstract : This is the first study assessing physician attitudes toward the integration of palliative care into pediatric oncology in 11 countries in Eurasia. This work reveals wide variability in the alignment of provider knowledge with World Health Organization guidelines and limited confidence in providing palliative care to children with cancer.